Comprehensive studies on microstructural, electronic, thermo-optical, mechanical and tribological behavious of vacuum heat treated ultra thin CP Ti foils. (18th July 2017) - Palai, Debajyoti; Dey, Arjun; Bera, Parthasarathi; Bhattacharya, Manjima; Mallick, Amitava Basu; Mukhopadhyay, Anoop Kumar; Sharma, Anand Kumar
Abstract: Present study reports the effect of vacuum (10 −5 mbar) heat treatment (300 °C–900 °C) on the microstructural, electronic, thermo-optical, mechanical and tribological properties of commercially pure (CP) titanium (Ti) ultra thin (75 µ m) foil. Phase analysis and surface morphology of the as-received and vacuum heat treated Ti foil samples were investigated by x-ray diffraction (XRD), field emission scanning electron microscopy (FESEM) and profilometry techniques. X-ray photoelectron spectroscopy (XPS) was employed to understand the electronic structure of the Ti foil surfaces. The solar absorptance ( α s ), solar reflectance ( ρ s ) and IR emittance ( ε ir ) of the as-received and vacuum heat treated Ti foil samples were evaluated. For vacuum heat treatment temperatures above 700 °C these properties were significantly altered. Nanoindentation study was carried out to evaluate hardness and elastic modulus while single pass scratch tests were performed to understand the tribological behaviour of the as-received and vacuum heat treated Ti foil samples. Further, yield strength and elongation of the as-received and vacuum heat treated Ti foil samples were measured from the tensile tests. Based on the experimental results it is suggested that the nanoindentation response of the as-received and vacuum heat treated Ti foil samples can be significantly affected by presence or absence of residual stress and pile-up around the nanoindents. Moreover, the results implied that possibly the formation of hard and brittle TiC phase during vacuum heat treatment temperature at and above 700 °C had influenced the thermo-optical, mechanical and tribological properties of the thin Ti foils.